A Rare Case of Concomitant Maxilla and Mandible Brown Tumours, Papillary Thyroid Carcinoma, Parathyroid Adenoma, and Osteitis Fibrosa Cystica - Thaís Borguezan Nunes; Sheyla Batista Bologna; Andréa Lusvarghi Witzel; Marcello Menta Simonsen Nico; Silvia Vanessa Lourenço (Hindawi Limited, 2016)
Objective. The brown tumour of hyperparathyroidism is a result of a metabolic disorder caused by primary hyperparathyroidism. Report. We described a case of a 37-year-old female patient presenting bimaxillary intraoral lesions and swelling in the neck. Incisional biopsy of the oral lesion was performed and histopathological examination revealed a central giant cell lesion composed by intense haemorrhagic exudate, abundant presence of giant cells, and areas with hemosiderin pigment. The patient also presented high levels of serum calcium and parathyroid hormone, hyperfunctioning parathyroid tissue, bilateral parenchymal nephropathy, and densitometry lower than expected, showing an advanced stage of osteitis fibrosa cystica. Synchronous parathyroid adenoma and papillary thyroid carcinoma were confirmed by imaging exams and histopathologically. Conclusion. The composition of all the clinical, pathological, and imaging findings led to the final diagnosis of brown tumour of hyperparathyroidism. The occurrence of parathyroid adenoma, papillary thyroid carcinoma, and brown tumours of hyperparathyroidism in their late stage (osteitis fibrosa cystica) associated with oral brown tumours involving the mandible and maxilla is extremely rare.